Copper-catalyzed enantioselective arylalkynylation of alkenes. Issue 6 (8th January 2020) - Lei, Guangyue; Zhang, Hanwen; Chen, Bin; Xu, Meichen; Zhang, Guozhu
Abstract : Enantioselective aryl and alkynylation of activated/nonactivated alkenes. Abstract : A copper-catalyzed enantioselective arylalkynylation of alkenes with diaryliodonium salt and a monosubstituted alkyne is reported. The three-component coupling reactions proceed under mild reaction conditions with a broad substrate scope, leading to synthetically valuable 1, 2-diaryl-3-butynes. The key to the success of this chemistry is the employment of the chiral bisoxazoline-phenylaniline (BOPA) ligand. A novel reaction pathway involving the phenyl radical generation under thermal copper catalysis is proposed according to mechanistic studies.